EMERGING DIGITAL TECHNOLOGIES IN ENGINEERING EDUCATION: PEDAGOGICAL POTENTIAL FOR ACTIVE LEARNING AND COMPETENCY DEVELOPMENT - da Cunha, Alex Pereira (Seven Editora, 2025)
Engineering education in the 21st century requires continuous modernization, driven by digital technologies and the demands of Industry 4.0. This article investigates how emerging technologies—virtual and remote laboratories, 3D printing, the Internet of Things, and immersive realities—contribute to active learning and competency development in engineering education. The study is based on an integrative literature review with a qualitative approach, analyzing 80 studies published between 2010 and 2025 through thematic content analysis. The results indicate that virtual and remote laboratories expand access to and safety in experimentation; 3D printing supports prototyping and the integration of theory and practice; IoT enables instrumentation, automation, and data analysis; and immersive realities enhance visualization and safe training. It is concluded that integrating these technologies with active methodologies, such as Project-Based Learning, is strategic for pedagogical innovation, provided it is supported by intentional curriculum planning and adequate faculty development. DOI: https://doi.org/10.56238/sevened2025.036-132